Celebrating Adam Watkins' Third Birthday at Special Spot - Watkins, Howard::::::::: (1981)
Marshall Chambers, Adam, Devon Bleile-Kratzer, Quentin Clay Clugston, Seth Tilley seated on big floor cushions